JAVANESE LANGUAGE OF BANTEN DIALECTS IN TANGERANG REGENCY - Agus Sulaiman (Journal of English Language and Literature (JELL), 2017)
The purpose of this study was to determine the phonological and morphological structure of the Java language dialect of Banten. The method used is descriptive-research. The researcher used methods into the field directly with data collection done by recording the written language and spoken language recording data. The study was conducted in the District Kronjo and Mekar Baru subdistrict, Tangerang. Both districts are predominantly speak dialects of Java Banten. The data described are living languages ​​and used in Tangerang. The data is sourced from the spoken language. The sample is done randomly based on the use of languages ​​in order to obtain sorts of the Java language dialect Banten. Informants were used as sources of information and data. This informants used in this study are (1) native speakers who settled in the area, (2) are not physically disabled, especially those associated with the pronunciation, and (3) have a good memory. For the validity of the data is taken at least two informants in every village. In addition to the informant, the informants also who have sufficient knowledge in the field of the realm of life to get certain vocabulary typical area of ​​Tangerang, so as to know the structure of the phonology and morphology of the Java language dialect Banten.